Empirical Testing of The Effects of Information Technology Literacy, Motivation, and Professional Ethics on Auditing Learning Among Accounting Students in Pontianak - Reni Dwi Widyastuti; Sartono Sartono; Wildasari Wildasari (Publikasi Indonesia, 2026)
Information technology is developing at a rapid pace, affecting the practice of accounting and, by extension, auditing. This study aims to measure the correlation and implications of information technology mastery in the learning process of auditing financial statements. Data collection employs both primary and secondary data. Primary data were gathered through questionnaires, while secondary data were derived from academic records. Data processing was carried out using regression analysis with the aid of SPSS software. The quantitative findings indicate that, when examined simultaneously, information technology mastery, learning motivation, and perception of professional ethics do not all significantly influence auditing learning among accounting students. Specifically, information technology mastery does not have a significant effect on auditing learning, learning motivation similarly does not have a significant effect, while professional ethics has a positive and significant effect on auditing learning. The qualitative findings further reveal that auditing learning practices have not been widely integrated with information technology, as auditing courses tend to emphasize manual conceptual understanding, standards-based audit procedures, and case study reports. Combining the quantitative and qualitative findings, it can be concluded that the success of auditing learning is not solely determined by motivation or technology mastery but is more fundamentally shaped by the internalization of professional ethical values.